Horrible Harry in Room 2B - Kline, Suzy (New York, NY : Puffin Books, 1998)
Doug discovers that though being Harry's best friend in Miss Mackle's second grade class isn't always easy, as Harry likes to do horrible things, it is often a lot of fun.